2015
DOI: 10.1017/s2040174415007977
|View full text |Cite
|
Sign up to set email alerts
|

Body adiposity and bone parameters of male rats from mothers fed diet containing flaxseed flour during lactation

Abstract: Obesity and osteoporosis may have their origins in early postnatal life. This study was designed to evaluate whether flaxseed flour use during lactation period bears effect on body adiposity and skeletal structure of male rat pups at weaning. At birth, male Wistar rats were randomly assigned to control and experimental (FF) groups, whose dams were treated with control or flaxseed flour diet, respectively, during lactation. At 21 days of age, pups were weaned to assess body mass, length and composition by dual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 28 publications
(58 reference statements)
1
21
0
Order By: Relevance
“…The present study showed that maternal intake of a flaxseed diet during lactation associated with exercise In a review study on the effects of flaxseed flour intake during pregnancy and lactation on the offspring's body mass at 21 days, 11 it was observed that the consumption of flaxseed flour in a concentration of 25% (25g flour/100g of feed) in the diet did not lead to changes in the animals' body mass at weaning, showing the same body mass as the animals of control rat dams. [21][22][23][24] In our study, although no statistically difference was found, a trend to lower body mass in animals of rat dams that consumed flaxseed diet during lactation was found. Other studies [25][26][27] reported lighter body mass of male offspring of rat dams who consumed flaxseed diet when compared to offspring of rat dams who consumed a control diet.…”
Section: Discussionmentioning
confidence: 60%
“…The present study showed that maternal intake of a flaxseed diet during lactation associated with exercise In a review study on the effects of flaxseed flour intake during pregnancy and lactation on the offspring's body mass at 21 days, 11 it was observed that the consumption of flaxseed flour in a concentration of 25% (25g flour/100g of feed) in the diet did not lead to changes in the animals' body mass at weaning, showing the same body mass as the animals of control rat dams. [21][22][23][24] In our study, although no statistically difference was found, a trend to lower body mass in animals of rat dams that consumed flaxseed diet during lactation was found. Other studies [25][26][27] reported lighter body mass of male offspring of rat dams who consumed flaxseed diet when compared to offspring of rat dams who consumed a control diet.…”
Section: Discussionmentioning
confidence: 60%
“…Within 24 hours of birth, excess pups were removed, and only six male pups were kept per dam, which maximizes lactation performance [6]. During lactation period, pups were randomly assigned: Control (C, n = 24), whose dams were fed with control diet containing 20 g casein, 52.95 g cornstarch, 7 g soybean oil and 5 g fiber per 100 g; experimental (F, n = 12), whose mothers were fed with diet containing 25 g flaxseed flour, 45.84 g cornstarch and 15 g casein per 100 g. Diets have same amounts of sucrose (20 g), mineral (3.5 g) and vitamin mix (1 g), L-cystine (0.3 g) and choline bitartrate (0.25g), per 100g [7]. During 21 days of lactation, free access to water and diets was not evaluated, due to difficulties in controlling pup food intake.…”
Section: Methodsmentioning
confidence: 99%
“…A similar result was found by Mucci et al (2015) who did not observe differences in male offspring body mass at 21 days of life in response to maternal intake during pregnancy and lactation of a diet with ground flaxseed accounting for 6 per cent of the lipid content when compared to the control group. Soares et al (2010), Leite et al (2012), Brant et al (2012) and da Costa et al (2016a offered during lactation, diet with 25 per cent of flaxseed and observed that both female and male offspring of these dams at weaning showed the same body mass when compared to the offspring of control dams. However, Cardozo et al (2010), Troina et al (2010) and Fernandes et al (2011), when analysing male offspring at weaning, observed a body mass reduction (p = 0.04, p < 0.05 and p < 0.05, respectively) when compared to offspring of dams who consumed control diet, and this finding agreed with Collins et al (2003), which showed that after providing diet with different defatted flaxseed concentrations, verified lower body mass in this offspring when compared to control group.…”
Section: Effects On Body Massmentioning
confidence: 99%
“…However, Cardozo et al (2010), Troina et al (2010) and Fernandes et al (2011), when analysing male offspring at weaning, observed a body mass reduction (p = 0.04, p < 0.05 and p < 0.05, respectively) when compared to offspring of dams who consumed control diet, and this finding agreed with Collins et al (2003), which showed that after providing diet with different defatted flaxseed concentrations, verified lower body mass in this offspring when compared to control group. Only one study observed higher body mass at 21 days of life in the male offspring of dams who consumed 25 per cent flaxseed diet when compared to control group (da Costa et al, 2016a(da Costa et al, , 2016b.…”
Section: Effects On Body Massmentioning
confidence: 99%